`He may not be qualified in it, but I think he`s still got the knowledge`: Team-doctoring in combat sports - AlHashmi, R.; Matthews, C. R. (International Review for the Sociology of Sport, 2022)
Several studies have examined the provision of medical care in a variety of competitive sport settings. These are important contributions, but the majority of this work has focused on elite sports that tend to have a group of medical health professionals as part of the team, with little attention given to sports that lack access to such services. This lack of dedicated medical support may result in athletes being more likely to engage in `team-doctoring` - a term used to describe athletes seeking medical advice from teammates and coaches. This concept is yet to be theorised and empirically described. In this paper, we begin to define, explore and contextualise the process of team-doctoring in relation to sociocultural interactions, beliefs embedded within the combat sport subculture and the critical role it plays in shaping fighters` perceptions of health and injury. In so doing, we demonstrate that team-doctoring is the process whereby apparent medical knowledge is (mis)understood, recommended, transferred, interpreted and developed within a somewhat coherent team.